The greatest salesman in the world. Part II, the end of the story : featuring the ten vows of success - Mandino, Og. (New York : Bantam Books, 1988)
The aging wise man Hafid secludes himself to write "The Ten Vows of Success" for posterity and is reunited with his young disciple Paul, now a great Apostle.
Keywords: Success -- Fiction